Odpowiedzi

2010-03-05T21:59:00+01:00
A) 3x+2x=10
5x=10/:5
x=2
b)-x-3(-2x)=5
-x+6x=5
5x=5/:5
x=1
c) x+y=7
x=y+1
y+1+y=7
2y=6/:2
y=3
x=3+1=4
d) 2x-y=4
x=11-y
2(11-y)-y=4
22-2y-y=4
-3y=-18/:(-3)
y=6
x=11-6=5
e)x-2y=3
2x=3y+8
x=2y+3
2(2y+3)=3y+8
4y+6=3y+8
y=2
x=2*2+3=7




1 5 1
2010-03-05T22:10:34+01:00
A)
3x+y=10
y=2x

y=10-3x
10-3x=2x

-5x=-10 /:(-5)
y=10-3x

x=2
y=10-3*2

x=2
y=4

b)
-x-3y=5
y=-2x

-x=5+3y /*(-1)
y=-2x

x=-5-3y
y=-2(-5-3y)

y=10+6y
x=-5-3y

-5y=10 /:(-5)
x=-5-3y

y=-2
x=-5-3*(-2)

x=-5+6
y=-2

x=1
y=-2

c)
x+y=7
x-y=1

x=7-y
7-y-y=1

-2y=1-7
x=7-y

-2y=-6 /:(-2)
x=7-y

y=3
x=7-3

x=4
y=3

d)
2x-y=4
x+y=11

-y=4-2x /*(-1)
x+y=11

y=-4+2x
x-4+2x=11

3x=11+4
y=-4+2x

3x=15 /:3
y=-4+2x

x=5
y=-4 \+2*5

x=5
y=-4+10

x=5
y=6


Ps. e nie umie sorki
2010-03-05T22:15:12+01:00
A) 3x+y=10
y=2x

3x+2x=10
5x=10 /:5
x=2

bo

5x=10
5*2= 10


b) -x-3y=5 /+x
y= -2x

-3y=5+x
-3(-2x)=5=x

6x=5+x /-x

5x=5

x=1
y= -2

bo
-1+6=5


c) x+y=7
x-y=1 / +y

x+y=7
x=1+y

1+y+y=7 /-1
2y=6
y=3
x=4
bo
4-3=1

d) 2x-y=4
x+y=11 /-y

2x-y=4
x=11-y

2(11-y)-y=4

22-3y=4 /-22

-3y=-18
3y=18

y=6
x=5

bo
10-6=4

e) x-2y=3
2x=3y+8
x=2y+3
2(2y+3)=3y+8
4y+6=3y+8
y=2
x=2*2+3= 7

ostatniego pewna nie jestam ale raczej dobrze;]